Rotational CARS thermometry and concentration measurements in ethane‐nitrogen mixtures using Fourier analysis. (14th February 2018) - Hosseinnia, Ali; Nordström, Emil; Fatehi, Hesameddin; Bood, Joakim; Bengtsson, Per‐Erik
Abstract: Rotational coherent anti‐Stokes Raman scattering (CARS) is an established diagnostic technique for thermometry and species concentration measurements of di‐atomics and tri‐atomics in combustion processes; however, studies on hydrocarbon fuel molecules have been scarce. In this work, we have investigated the diagnostic potential for rotational CARS on ethane with emphasis on concentration measurements in mixtures with nitrogen. Rotational CARS spectra have periodic line structures, and because ethane and nitrogen spectra partially overlap, a novel Fourier analysis approach was developed and applied to facilitate evaluation of relative concentrations and temperatures. Instead of the standard procedure of spectral fitting using libraries of theoretically calculated spectra, the fitting was based on an experimental database of temperatures and relative ethane/nitrogen concentrations. The method was successfully demonstrated in an ethane diffusion flame where ethane, initially at room temperature, is heated downstream as well as mixed with increasing amounts of nitrogen. The evaluated temperatures and concentrations are in good agreement with computational fluid dynamic model simulations. Abstract : In this paper, we present rotational coherent anti‐Stokes Raman scattering measurements of ethane concentration and temperature in ethane/nitrogen mixtures. A novel Fourier analysis approach was developed to facilitate the evaluation of partially overlapping ethane and nitrogen spectra with periodic line structures. The evaluation procedure was based on an experimental database of temperatures and relative ethane/nitrogen concentrations. The methods were applied on an ethane diffusion flame, and the results were compared with results from a computational fluid dynamic model.